Recruiting to surgical trials in the emergency setting: using a mixed methods study to understand clinician and patient perspectives. Issue 6 (23rd November 2022) - Twiddy, Maureen; Birtwistle, Jacqueline; Edmondson, Amanda; Croft, Julie; Gordon, Kathryn; Meads, David; Burke, Dermot; Griffiths, Ben; Rose, Azmina; Sagar, Peter; Stocken, Deborah; Brown, Julia M B; et al.
Abstract: Background: Undertaking randomized clinical trials (RCTs) in emergency surgical settings is associated with methodological and practical challenges. This study explored patients' and clinicians' perspectives associated with the conduct of an RCT comparing laparoscopic and open colorectal surgery in the acute setting. Methods: All eligible patients screened and enrolled for the 'Laparoscopic versus open colorectal surgery in the acute setting (LaCeS)' multicentre, randomized clinical feasibility trial in five UK NHS Trusts were invited to respond to a survey. Patients and healthcare professionals were also invited to take part in semi-structured interviews. Survey and interviews explored the acceptability of the feasibility trial. Interviews were audio recorded, transcribed verbatim, and analysed using thematic analysis. Survey data were analysed descriptively to assess patient views of the trial and intervention. Results: Out of 72 patients enrolled for the LaCeS RCT, survey data were collected from 28 patients (38.9 per cent), and interviews were conducted with 16 patients and 14 healthcare professionals. Thirteen out of 28 patients (46 per cent) had treatment preferences but these were not strong enough to deter participation. Twelve of the patients interviewed believed that their surgeon preferred laparoscopic surgery, but this did not deter them from participating in the trial. Half of the surgeons interviewed expressed the view that laparoscopic surgery was of benefit in this setting, but recognized that the need for research evidence outweighed their personal treatment preferences. Eight of the 14 recruiters reported that the emergency setting affected recruitment, especially in centres with fewer recruiting surgeons. Interviewees reported that recruitment was helped significantly by using surgical trainees to consent patients. Conclusion: This study identified specific challenges for the LaCeS trial design to address and adds significant insights to our understanding of recruiting to emergency surgical trials more broadly. Abstract : This paper presents the findings of a mixed-methods study exploring patient and clinician views of participating in the LaCeS trial, comparing laparoscopic and open colorectal surgery in the acute setting. Patients found the trial and intervention acceptable, but the emergency setting affected recruitment.